Hybrid Strategies: Allocating Involvement in the Digital Age. Issue 3 (16th June 2015) - Benediktsson, Mike Owen; Alexander, Daniel; Bermeo, Jhanidya; Contreras, Joseph; Kingston, Bradley; Harper, Wendy; Henkin, Jonathan; Lopez, Fausto; Wagenheim, Randy; Williams, Aaron
<x xml:space="preserve">Abstract</x> An important trait of mobile phones is their capacity to superimpose multiple social interactions in time and space. Little research examines how individuals choose between face‐to‐face and digitally mediated interactions in specific social contexts. Drawing upon focus group interviews with a diverse sample of university students in the United States, we argue that, contrary to a perspective that is popular in theory and journalistic commentary, mobile phone users do not experience the digital and the face‐to‐face as distinct realms. In deciding where to direct their attention, users enmesh the distant and the present, making moves that are expressive and strategic in their own right that reveal the interest, intimacy and urgency that users place in multiple, coinciding social involvements.